Experimental and theoretical investigations on fullerene (C60) induced compact CH3NH3PbI3 perovskite thin films. (1st July 2022) - Kumar, Virendra; Pandey, Anand; Kumar, Lokendra; Singh, Manohar; Kumar, Ashwani; Kishor, Shyam; Jain, Kalpna; Singh, Khundrakpma Saratchandra; Singh, Beer Pal
Abstract: In the present work, pure and Fullerene (C60 )-doped methyl ammonium lead halide (CH3 NH3 PbI3 ) perovskite thin films were prepared on glass substrates by spin coating method at different concentrations of fullerene (C60 ).The structural, morphological, and optical characteristics of as-prepared thin films were analysed using experimental and computational methods. The X-ray diffraction studies and their Reitveld refinement analysis of the samples confirms that all deposited perovskite thin films have tetragonal structure and are highly oriented along the (110) plane. The morphology of the perovskite films was investigated by field emission scanning electron microscope (FE-SEM). The elemental composition of perovskite thin films was confirmed by Energy Dispersive X-rays Analysis (EDAX). The addition of fullerene (C60 ) resulted in the increase of grain size sand a more compact surface development of the perovskite thin films with fewer flaws as compared with perovskite thin films without (C60 ) was evaluated. Also, geometrical, electronic and optical properties were studied by using the first principles DFT computational method. Optical properties have been studied experimentally and verified computationally. All the perovskite thin film samples exhibit direct band-gap which is suitable for solar cells applications.